Evaluasi Penyelenggaraan Pelatihan Jarak Jauh Tata Naskah Dinas di Balai Diklat Keagamaan Banjarmasin: Analisis Model Kirkpatrick Level 1 - Amalia, Jadwa (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2022)
This article describes the results of research on participants' assessments of the organizers and facilitators involved in PJJ Tata Naskah Dinas in the Kankemenag Kab. Barito Utara organized by BDK Banjarmasin. This study used a survey method with 30 respondents. Data were collected using a questionnaire with a Likert scale and processed using descriptive statistical techniques. The results obtained indicate that the highest average score for the assessment of the facilitator is in the statement item regarding the ethics and attitudes of the facilitators and the language used, while the lowest average score is in the statement item regarding the achievement of the learning objectives and the learning methods used. For the assessment of the organizers, the highest average value was in the item of the benefit obtained by the participants, while the lowest average value was in the statement item regarding the learning management system (LMS) facility used.